The effect of perceptual-cognitive skills in college elite athletes: an analysis of differences across competitive levels - Wu, K.- C.; Lin, H.- C.; Cheng, Z.- Y.; Chang, C.- H.; Chang, J.- N.; Tai, H.- L.; Liu, S.- I. (Sports, 2025)
Background: Athletes with expertise in sports show extensive procedural and factual information, enhancing their ability to focus attention, use cues, and anticipate events. This study examined the differentiation of perceptual-cognitive skills by focusing on attentional cues, processing speed, and working memory.